Occurrence of different gynandromorphs and ergatandromorphs in laboratory colonies of the urban ant, Monomorium floricola - Campos, Ana E. De C.; Kato, Luciane M.; De Zarzuela, Maria F. M. [UNESP] (Oxford University Press (OUP), 2011)
Colonies of Monomorium floricola (Jerdon) in laboratory conditions showed gynandromorphic and ergatandromorphic specimens, the former with nine different combinations of male and female tissues and the latter with 6 different combinations. Their development from egg to adult was around 74.6 days for gynandromorphs, and 87.5 days for ergantandromorphs.
Keywords: Formicidae; longevity